Click and Click‐Inspired Chemistry for the Design of Sequence‐Controlled Polymers. Issue 24 (9th October 2017) - Martens, Steven; Holloway, Joshua O.; Du Prez, Filip. E.
Abstract: During the previous decade, many popular chemical reactions used in the area of "click" chemistry and similarly efficient "click‐inspired" reactions have been applied for the design of sequence‐defined and, more generally, sequence‐controlled structures. This combination of topics has already made quite a significant impact on scientific research to date and has enabled the synthesis of highly functionalized and complex oligomeric and polymeric structures, which offer the prospect of many exciting further developments and applications in the near future. This minireview highlights the fruitful combination of these two topics for the preparation of sequence‐controlled oligomeric and macromolecular structures and showcases the vast number of publications in this field within a relatively short span of time. It is divided into three sections according to the click‐(inspired) reaction that has been applied: copper‐catalyzed azide–alkyne cycloaddition, thiol‐X, and related thiolactone‐based reactions, and finally Diels–Alder‐chemistry‐based routes are outlined, respectively. Abstract : Click‐inspired reactions have been shown to be powerful chemistry platforms for the synthesis of sequence‐controlled polymers. Such precision polymers are actually pushing the application boundaries of synthetic polymers further than ever.